2004
DOI: 10.1542/peds.2004-0124
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium septicum Myonecrosis in Congenital Neutropenia

Abstract: ABSTRACT. Severe congenital neutropenia (SCN) andClostridium septicum myonecrosis is an uncommon and life-threatening association requiring urgent combined aggressive medical and surgical management. We report 2 cases of SCN (1 with known Kostmann's syndrome and 1 not known at presentation to have a congenital neutropenic disorder but subsequently received a diagnosis of cyclic neutropenia) who presented with spontaneous C septicum myonecrosis. The cases highlight the importance of response to recombinant huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In atraumatic gas gangrene, infection occurs at distal sites or when there is a breach in the gastrointestinal barrier [ 3 ]. Infection primarily occurs in severely immunocompromised hosts; C. septicum is a major cause of infection in adults with severe hematological malignancies and colorectal cancer, as well as in children with severe neutropenia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In atraumatic gas gangrene, infection occurs at distal sites or when there is a breach in the gastrointestinal barrier [ 3 ]. Infection primarily occurs in severely immunocompromised hosts; C. septicum is a major cause of infection in adults with severe hematological malignancies and colorectal cancer, as well as in children with severe neutropenia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that early use of G-CSF may improve the outcome of clostridial infections in neutropenia. 10 Our patient received subcutaneous G-CSF since the day of admission, but exhibited no significant increase in leukocyte count.…”
Section: Discussionmentioning
confidence: 67%
“…A torsed colonic polyp was found in a recently reported pediatric case of C. septicum infection [18]. Congenital neutropenia and leukemia comprise other conditions in which C. septicum has been described [18,30]. Gastrointestinal pathology in these settings also appears to be the prime site of invasion.…”
Section: Discussionmentioning
confidence: 99%